2020
DOI: 10.1590/1980-57642020dn14-020001
|View full text |Cite
|
Sign up to set email alerts
|

Daily functioning and dementia

Abstract: Abstract. Dementia is characterized by a decline in memory, language, problem-solving and in other cognitive domains that affect a person’s ability to perform everyday activities and social functioning. It is consistently agreed that cognitive impairment is an important risk factor for developing functional disabilities in patients with dementia. Functional status can be conceptualized as the ability to perform self-care, self- maintenance and physical activity. A person with dementia usually requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 92 publications
0
51
0
6
Order By: Relevance
“…Impairments in basic ADLs and more complex, instrumental ADLs (IADLs) are associated with the development of functional disability. [34][35][36][37][38] In a systematic review, Gaugler et al 39 found that having three or more ADL dependencies was a strong predictor of nursing home admission. In addition, IADL impairment may adversely affect the management of risk factors such as hypertension and diabetes, which are risk factors for heart failure.…”
Section: Activities and Participationmentioning
confidence: 99%
“…Impairments in basic ADLs and more complex, instrumental ADLs (IADLs) are associated with the development of functional disability. [34][35][36][37][38] In a systematic review, Gaugler et al 39 found that having three or more ADL dependencies was a strong predictor of nursing home admission. In addition, IADL impairment may adversely affect the management of risk factors such as hypertension and diabetes, which are risk factors for heart failure.…”
Section: Activities and Participationmentioning
confidence: 99%
“…The following neuropsychological data were collected from all participants: Mini-Mental State Examination (MMSE); Alzheimer's Disease Assessment Scale – Cognitive subscale (ADAS-Cog); F-A-S Letter Verbal Fluency (LVF) [or Controlled Oral Word Association Test (COWAT)]; Logical Memory subtest of the Wechsler Memory Scale (WMS) – fourth edition (WMS-IV). In addition, data with the Lawton Instrumental Activities of Daily Living Scale (LADL) and Neuropsychiatric Inventory (NPI) were collected and included in this study, as behavioral disturbance and loss of daily functioning are common in AD patients and can be assessed by these two tests (Cipriani et al, 2020 ; Cummings, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Para além das orientações dos protocolos do Ministério da Saúde, o idoso com demência tem particularidades que podem tornar este cuidado um grande desafio. À medida que a doença evolui, aumenta o declínio nas atividades de cuidado pessoal, com prejuízo nos cuidados com a higiene corporal (Cipriani 2020), sendo este um dos riscos identificados num estudo (Evans 2018). Com o aumento da dependência nas atividades da vida diária, é necessário que o cuidador /familiar gerencie este cuidado, que muitas vezes é agravado pelo déficit de memória e pelos sintomas psicológicos e comportamentais da demência.…”
Section: Risco De Infecções Associadas Aos Cuidados De Saúdeunclassified
“…Nas demências, a deterioração cognitiva progressiva tem um grande impacto na capacidade de realizar as atividades diárias. A cognição está associada a realização das atividades do cotidiano (Cipriani 2020) A cognição compreende a aquisição de conhecimento e compreensão através de domínios cognitivos que envolvem atenção, percepção, memória, linguagem e funções executivas (Cipriani 2020). Para a realização de uma única atividade funcional são necessários vários domínios cognitivos.…”
Section: Risco De Perda Funcional Associada Ao Déficit Cognitivounclassified
See 1 more Smart Citation